Velocity Structure of Circumstellar Environment around Class 0/I Protostars: Uncertainty in the Protostellar Mass Estimation Using Circumstellar Velocities - Shingo Hirano; Yuri Aikawa; Masahiro N. Machida (The Astrophysical Journal)
Recent high-resolution observations have enabled detailed investigations of the circumstellar environments around Class 0/I protostars. Several studies have reported that the infall velocity of the envelope is a few times smaller than the freefall velocity inferred from protostellar masses estimated via the observed rotational velocity of their Keplerian disks. To explore the physical origins of the slow infall, we perform a set of three-dimensional resistive magnetohydrodynamic simulations of the star formation process, extending to 10 ^5 yr after protostar formation. Our simulations show that the infall velocity decreases markedly at the outer edge of the pseudodisk (at radii of ∼100–1000 au) and is much slower than the expected freefall velocity. The degree of this reduction depends on (1) the initial magnetic field strength, (2) the alignment between the initial field and the rotation axis, and (3) the evolutionary stage of the system. Across our parameter space, the ratio of the infall velocity to the freefall velocity is as small as 0.2–0.5, which is consistent with the observations. We further examine the reliability of protostellar mass estimates derived from infall and rotational velocities. While the mass derived from disk rotation closely matches the true value, deviation by a factor of 0.3–2 is found for the estimates using the infall velocity; it is underestimated due to slow infall, but could also be overestimated due to the contribution of disk mass. These findings underscore the critical role of magnetic fields in shaping star formation dynamics and highlight the uncertainties associated with protostellar mass estimates.